2010
DOI: 10.1037/a0019244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pramipexole on impulsive choice in male wistar rats.

Abstract: Clinical reports, primarily with Parkinson's patients, note an association between the prescribed use of pramipexole (and other direct-acting dopamine agonist medications) and impulse control disorders, particularly pathological gambling. Two experiments examined the effects of acute pramipexole on rats' impulsive choices where impulsivity was defined as selecting a smallersooner over a larger-later food reward. In Experiment 1, pramipexole (0.1 to 0.3 mg/kg) significantly increased impulsive choices in a cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 60 publications
4
38
1
1
Order By: Relevance
“…While acute PPX increases response latencies in both humans (Hamidovic, Kang, & de Wit, 2008) and nonhumans (Johnson, Madden, Brewer, Pinkston, & Fowler, 2011; Koffarnus et al, 2011; Madden et al, 2010), repeated administration may normalize these sedative effects (Riddle et al, 2012). We therefore examined the drug effect on mean left- and right-lever latencies in both assessments using three-way repeated-measures ANOVA (Delay Condition, Dose, Lever).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While acute PPX increases response latencies in both humans (Hamidovic, Kang, & de Wit, 2008) and nonhumans (Johnson, Madden, Brewer, Pinkston, & Fowler, 2011; Koffarnus et al, 2011; Madden et al, 2010), repeated administration may normalize these sedative effects (Riddle et al, 2012). We therefore examined the drug effect on mean left- and right-lever latencies in both assessments using three-way repeated-measures ANOVA (Delay Condition, Dose, Lever).…”
Section: Methodsmentioning
confidence: 99%
“…Madden, Johnson, Brewer, Pinkston, and Fowler (2010, Experiment 1), for example, administered PPX (0.1, 0.18, & 0.3 mg/kg) prior to sessions in which rats chose repeatedly between SSRs and LLRs. In their “self-control” baseline, the delay to the LLR was adjusted until SSR choice was infrequent (≤ 20%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the DA D2/D3 receptor agonist, pramipexole, as well as other DA receptor agonists have been implicated in the emergence of risk-seeking behaviors, such as pathological gambling in multiple case reports and cross-sectional studies in patients with Parkinson's disease (PD) (Bodi et al, 2009;Dodd et al, 2005;Lader, 2008;Pontone et al, 2006;Potenza et al, 2007;Voon et al, 2006aVoon et al, , 2006bWeintraub et al, 2006Weintraub et al, , 2010. A purported mechanism for this effect is related to pramipexole's high selective affinity for D3 receptors, which are primarily expressed in the mesocorticolimbic DA pathway-a circuitry that is active during impulsive decision making (Madden et al, 2010). Indeed, several studies that have used pramipexole in single-dose challenge paradigms have confirmed its actions on rewardrelated neural networks, primarily at low doses and in healthy individuals (Riba et al, 2008;Ye et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Although several studies, in both animals and humans, have demonstrated beneficial cognitive effects of pro-dopaminergic agents on measures of attention and working memory (Costa et al, 2009;Granon et al, 2000;Mattay et al, 2000;Mehta et al, 2000), there have also been reports of rare but concerning side effects, including induced impulse-control disorders in individuals with no prior history of such difficulties (Dodd et al, 2005;DriverDunckley et al, 2007;Giovannoni et al, 2000;Klos et al, 2005;Madden et al, 2010;McKeon et al, 2007;Munhoz et al, 2009;Potenza et al, 2007;Riba et al, 2008;Voon et al, 2006b;Weintraub et al, 2006). For example, the DA D2/D3 receptor agonist, pramipexole, as well as other DA receptor agonists have been implicated in the emergence of risk-seeking behaviors, such as pathological gambling in multiple case reports and cross-sectional studies in patients with Parkinson's disease (PD) (Bodi et al, 2009;Dodd et al, 2005;Lader, 2008;Pontone et al, 2006;Potenza et al, 2007;Voon et al, 2006aVoon et al, , 2006bWeintraub et al, 2006Weintraub et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%